PROGRAM COMPLEX OF THE MULTICRITERIA COMPARATIVE ANALYSIS OF ECONOMIC SYSTEMS - Dmitri N. Lapaev; Evgenii S. Mityakov; Evgeny A. Kornev (Статистика и экономика)
The paper describes the software system of multi-criteria analysis of comparative economic systems - agraphical environment, which includes software andgraphical implementation of six algorithms (modules)of the multi-criteria analysis. To check the adequacy of the results of the program algorithms are comparedwith manual calculations.